How to Produce and Measure Throughput Legitimacy? Lessons from a Systematic Literature Review - Vincent Caby; Lise Frehen (Politics and Governance, 2021)
After two decades of research on throughput legitimacy, making sense of the stock of accumulated knowledge remains a challenge. How can relevant publications on throughput legitimacy be collected and analysed? How can the level of throughput legitimacy be measured? Which policy activities contribute to the production of throughput legitimacy? To answer these questions, we designed and implemented an original systematic literature review. We find that the measurement of the level of throughput legitimacy introduces a number of problems that call for the systematic and rigorous use of a more complete set of precise, specific indicators to advance the theory of throughput legitimacy. A number of participatory decision-making activities contribute to the production of throughput legitimacy. Engaging in these activities is not without risk, as variations in throughput legitimacy affect input and output legitimacy. To prevent vicious circles, lessons can be drawn from the literature on collaborative governance and decision-makers’ strategies to support effective collaboration between stakeholders.